The Effect of 3-Month Contraceptive Injections on the Smoothness of Breastfeeding Among Mothers in the Sudiang Health Center Area Makassar City - Asri, Amanda; Andi Alifia Ayu Delima; Arlina Wiyata Gama (Comprehensive Health Care, 2024)
Breast milk is the best food for infants, especially during the first 6 months (exclusive breastfeeding) and continued up to 2 years. Breastfeeding is the best way to meet nutritional needs. However, many mothers still cannot breastfeed their children properly. One of the biggest obstacles is insufficient or no breast milk at all. Many factors influence the smoothness of breastfeeding, one of which is contraceptives. Contraceptives are drugs used to prevent pregnancy. This study aims to analyze the effect of 3-month contraceptive injections on the smoothness of breastfeeding among mothers at the Sudiang Health Center in Makassar City. This type of research is an analytical survey with a case-control approach. The population in this study was 342, from which 184 samples were taken from January to June 2022. Univariate and bivariate analysis techniques were used to analyze the data. This study used SPSS 23, with a chi-square test, and obtained a p-value of 0.000, which means there is a significant effect of the 3-month contraceptive injection on the smoothness of breastfeeding among mothers in the Sudiang Health Center area, Makassar City.